The Experience of Unemployment
XI, 204 p.
Keywords: Increasingly high unemployment has brought with it a multitude of consequences affecting those without jobs and, beyond them, their families, friends and communities. This book reports findings from original research. It explores, often in the words of the unemployed and others involved, what life without a job is like. It challenges many widely held beliefs about the unemployed - that they are workshy, price themselves out of jobs or earn money illegally on the side - and explores where such misconceptions come from. It reveals the inherent contradictions involved in trying to search for work whilst coping with the experience of unemployment.